2019
DOI: 10.21203/rs.2.289/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasound-guided quadratus lumborum block for postoperative pain control in patients undergoing unilateral inguinal hernia repair, a comparative study between two approaches.

Abstract: Background : early postoperative ambulation and reduction of hospital stay necessitate efficient postoperative analgesia. Quadrates Lumborum Block (QLB) has been described to provide adequate postoperative analgesia after abdominal surgery. This randomized comparative trial was designed to compare the duration of analgesia provided by two different QLB approaches; the posterior QLB (QLB-2) and transmuscular QLB (QLB-3) in patients undergoing surgical repair of unilateral inguinal hernia. Methods: Forty patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We also found that posterior QLB significantly prolonged the time to the first opioid requirement. The median time to the first compression of the analgesic pump in the intervention group was significantly longer than in the control group, about 18 h. In the trials of Li et al (12) and Ahmed et al (22), the median time to the first compression of the analgesic pump was 13.5 h and 12 h, respectively. This difference may be related to multimodal analgesia's type or the dose of other analgesics.…”
Section: B Amentioning
confidence: 89%
“…We also found that posterior QLB significantly prolonged the time to the first opioid requirement. The median time to the first compression of the analgesic pump in the intervention group was significantly longer than in the control group, about 18 h. In the trials of Li et al (12) and Ahmed et al (22), the median time to the first compression of the analgesic pump was 13.5 h and 12 h, respectively. This difference may be related to multimodal analgesia's type or the dose of other analgesics.…”
Section: B Amentioning
confidence: 89%
“…Previous studies have shown both the TAP block and the anterior QLB to be effective in lowering postoperative pain score and opioid consumption in inguinal repair 4,5 . Ahmed et al 5 found that the anterior QLB significantly lowered postoperative pain scores immediately after arrival in the PACU and after 12 h. A meta‐analysis looking at the duration of a lateral and a posterior TAP showed a reduction of opioid consumption, rest and dynamic pain up to 48 h 16 …”
Section: Discussionmentioning
confidence: 99%
“…Both the TAP block and the anterior Quadratus lumborum (QLB) have been shown to reduce postoperative pain and opioid consumption after laparoscopic inguinal hernia repair 4–6 . The TAP block can be performed using several approaches: subcostal, lateral and posterior 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a longer duration of block in transmuscular QL block group as compared to posterior QL block group (20.1 ± 6.2 versus 12.0 ± 4.8 h, respectively) with a P value of <0.001. Although the authors concluded that total morphine consumption was reduced in the posterior QL group (1.9 ± 0.6 mg versus 1.1 ± 0.9 mg) than in the transmuscular QL group over 24 h,[ 22 ] it does not satisfy aclinically meaningful difference. The present study as compared to that of Ahmed et al .…”
Section: Discussionmentioning
confidence: 99%